Intensive Care Nurses\' Experiences of Moral Distress in the COVID-19 Pandemic - Fereshteh Araghian Mojarad; Vida Shafipour (Journal of Mazandaran University of Medical Sciences, 2023)
Background and purpose: As direct and continuous care providers to patients, nurses face various types of psychological stress in the work environment more than other groups. Meanwhile, moral distress in special care units is much more impressive. This study aimed to explain the moral distress experienced by nurses that provided care to patients with COVID-19 patients in special care units. Materials and methods: We performed a conventional qualitative content analysis in 2020-2021. The study population included nurses caring for COVID-19 patients in special care units selected by purposive sampling in educational hospitals affiliated with Mazandaran University of Medical Sciences. In-depth, semi-structured interviews were carried out for data collection. Graneheim and Lundman qualitative approach was used to analyze the data. The trustworthiness of the study was assessed by Guba and Lincoln's stringent criteria. Results: In this study, 14 nurses (25-48 yeas of age) were interviewed. We found three main layers and eight sub-layers, including multiple annoyances (mental and physical stress, negative effects on family and friends relationships, negative effects on professional work), work pressure (hard conditions of the patient and companion, difficulty and work stress, weak management), and persistence and adaptation (self-protection, coping with difficult conditions). Conclusion: Based on this study, nurses should be encouraged to express their feelings so that they can establish a balance between the difficulty of ethical decisions and meeting the patient's needs and managing their emotions.